SARS‐CoV‐2 B.1.1.7 variant of concern detected in a pet dog and cat after exposure to a person with COVID‐19, USA. Issue 3 (12th May 2021) - Hamer, Sarah A.; Ghai, Ria R.; Zecca, Italo B.; Auckland, Lisa D.; Roundy, Christopher M.; Davila, Edward; Busselman, Rachel E.; Tang, Wendy; Pauvolid‐Corrêa, Alex; Killian, Mary Lea; Jenkins‐Moore, Melinda; Torchetti, Mia Kim; et al.
Abstract: As part of a longitudinal household transmission study of pets living with persons with COVID‐19 in Texas, two pets were confirmed to be infected with the SARS‐CoV‐2 B.1.1.7 variant of concern (VOC). The pets were a dog and a cat from the same household, sampled two days after their owner tested positive for COVID‐19. The oral, nasal and fur swabs for both pets tested positive for SARS‐CoV‐2 by qRT‐PCR and consensus whole‐genome sequences from the dog and cat were 100% identical and matched the B.1.1.7 VOC. Virus was isolated from the cat's nasal swab. One month after initial detection of infection, the pets were re‐tested twice at which time only the fur swabs (both pets) and oral swab (dog only) remained positive, and neutralizing antibodies for SARS‐CoV‐2 were present in both animals. Sneezing by both pets was noted by the owner in the weeks between initial and follow‐up testing. This study documents the first detection of B.1.1.7. in companion animals in the United States, and the first genome recovery and isolation of B.1.1.7 variant of concern globally in any animal.